2009
DOI: 10.3892/ijo_00000277
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma: Molecular pathogenesis and emerging target therapies (Review)

Abstract: Abstract. Malignant melanoma is an aggressive tumor of the skin with a poor prognosis for patients with advanced disease. It is resistant to current therapeutic approaches. In melanoma, both the Ras/Raf/MEK/ERK (MAPK) and the PI3K/AKT (AKT) signalling pathways are constitutively activated through multiple mechanisms. Mutations of BRAF have been proposed to contribute to melanoma development. Increased activity of the MAPK pathway prevents apoptosis and induces cell cycle progression. PTEN deletion results in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 101 publications
(127 reference statements)
0
12
0
2
Order By: Relevance
“…Матриксным металлопротеиназам (ММП) отводится ключевая роль в развитии процессов инвазии и метастазирования [1,2]. ММП выполняют как деструктивную, так и важнейшие регуляторные функции, активируя, инактивируя и модифицируя целый ряд биологически-активных молекул [3,4].…”
Section: Introductionunclassified
“…Матриксным металлопротеиназам (ММП) отводится ключевая роль в развитии процессов инвазии и метастазирования [1,2]. ММП выполняют как деструктивную, так и важнейшие регуляторные функции, активируя, инактивируя и модифицируя целый ряд биологически-активных молекул [3,4].…”
Section: Introductionunclassified
“…Melanomas are malignant tumors arising on pigment-producing melanocytes mainly located in the epidermis of the skin but also in other anatomic districts, and comprise about 4.3% of all new cancers [1]. In Sardinia, the incidence of melanoma is roughly 4 new cases per 100,000 inhabitants per year [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have shown that among many types of MMPs, especially type IV collagenase MMP-2, -9 are UV inducible factors in the final degradation of collagen fibrillar after initial cleavage by collagenase (15)(16)(17)(18). Regulation of MMP expression is related with inhibitors of MMPs (TIMPs).…”
Section: Resultsmentioning
confidence: 99%